Development of nitride-based optical phased array at 1092 nm for the optical addressing of ⁸⁸Sr+ Ion - Lim, Yu Dian (2023)
Optical phased array (OPA) structures are designed and fabricated for the optical addressing of trapped 88Sr+ ions. Laser light of 1092 nm wavelength corresponding to the 2D3/2 to 2P1/2 of 88Sr+ ion is used, where silicon nitride (SiN) platform with integrated titanium nitride (TiN) thermos-optic heaters are selected. Beam steering of ~33 µm, which corresponds to ~11.6° steering angle, is obtained by applying 10V on alternative TiN heaters in the 8-Channel OPA structure.